Mycobacterium tuberculosis infection of the 'non‐classical immune cell'. Issue 9 (28th April 2015) - Randall, Philippa J; Hsu, Nai‐Jen; Quesniaux, Valerie; Ryffel, Bernhard; Jacobs, Muazzam
Abstract : Mycobacterium tuberculosis can infect 'non‐classical immune cells', which comprise a significant constituency of cells that reside outside of those defined as 'classical immune cells' from myeloid or lymphoid origin. Here we address the influence of specific 'non‐classical immune cells' in host responses and their effects in controlling mycobacterial growth or enabling an environment conducive for bacilli persistence. The interaction of M. tuberculosis with epithelial cells, endothelial cells, fibroblasts, adipocytes, glia and neurons and downstream cellular responses that often dictate immune regulation and disease outcome are discussed. Functional integration and synergy between 'classical' and 'non‐classical immune cells' are highlighted as critical for determining optimal immune outcomes that favour the host.